N(1)-Nonyl-1,4-diaminobutane ameliorates brain infarction size in photochemically induced thrombosis model mice - Masuko, Takashi (Neurosci Lett, 2018)
Inhibitors for polyamine oxidizing enzymes, spermine oxidase (SMOX) and N(1)-acetylpolyamine oxidase (PAOX), were designed and evaluated for their effectiveness in a photochemically induced thrombosis (PIT) mouse model. N(1)-Nonyl-1,4-diaminobutane (C9-4) and N(1)-tridecyl-1,4-diaminobutane (C13-4) competitively inhibited the activity of PAOX and SMOX in a manner comparable to N(1),N(4)-bis(2,3-butadienyl)-1,4-butanediamine (MDL72527), an irreversible inhibitor of both enzymes. The two compounds were then tested for their effects in the PIT model. Both intraperitoneal (i.p.) and intracerebroventricular (i.c.v.) administration of C9-4 decreased infarct volumes significantly. By contrast, C13-4 reduced the volume of brain infarction by i.c.v. administration, but no reduction was observed after i.p. administration. C9-4 administered by i.p. injection reduced the volume of brain infarction significantly at doses of more than 3 mg/kg, and the dosage of 5 mg/kg or 10 mg/kg demonstrated the most potent effect and were more effective than equivalent doses of the other inhibitors such as MDL72527 and N-benzylhydroxylamine. I.P. injection of 5mg/kg of C9-4 provided a therapeutic time window of longer than 12 h. This report demonstrates that C9-4 is a potent inhibitor of the polyamine oxidizing enzymes and is useful lead compound for candidate drugs with a long therapeutic time window, to be used in the treatment of ischemic stroke.